Studi Karakter Mutu Buah Pepaya IPB - Ketty Suketi; Roedhy Poerwanto; Sriani Sujiprihati; , Sobir; Winarso D.Widodo (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2010)
ABSTRACTThe objective of the experiment was to investigate the physical and chemical characteristic of eight genotypes of papaya i.e. IPB1, IPB 2A, IPB 3, IPB 3A, IPB 4, IPB 7, IPB 8, and IPB 9 on two stages of ripening period based on percentage of the yellow area of fruit peel (75% yellow and 100% yellow). The fruits were picked at 25% yellow of fruit peel colour. The experiment was conducted in split plot wi th completely randomized block design. The main plot was ripening periods of 75% and 100% ripe, while the genotypes were taken at subplot. There was no significant different on physical and chemical characteristics between papaya at stadium 75% and 100% yellow. Flesh firmness of IPB 9 was better than IPB 1, IPB 4 and IPB 8. Ascorbic acid content of IPB 4 (107.36 mg/100 g) was higher than that of IPB 2A and IPB 3A. Carotenoid content of IPB 4 (29. 73 mg/100g) was higher than that of the other genotypes.Key words: Carica papaya, physical characteristic, chemical characteristic, ascorbic acid, carotenoid